1998
DOI: 10.2172/574233
|View full text |Cite
|
Sign up to set email alerts
|

Results of Phase I groundwater quality assessment for single-shell tank waste management areas T and TX-TY at the Hanford Site

Abstract: This report was prepared as an account of work sponsored by an agency of the United States Government. Neither the United States Government nor any agency thereof, nor any of their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial product, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 3 publications
2
52
0
Order By: Relevance
“…In addition, variation of concentrations with the changing direction of groundwater flow indicates a source within the southern portion of the W'MA. Ratios of mobile contaminants (e.g., chromium, nitrate, technetium-99, tritium) are useful in identifying tank waste components and mixing trends in groundwater (Johnson and Chou 1998;Hodges 1998). Plots of nitrate/technetium-99 versus technetium-99 ( Figure 5.2) indicate that the data is consistent with the observed groundwater contamination being the result of mobilization and dilution of tank waste by infiltrating surface water.…”
Section: Conceptual Modelmentioning
confidence: 57%
See 1 more Smart Citation
“…In addition, variation of concentrations with the changing direction of groundwater flow indicates a source within the southern portion of the W'MA. Ratios of mobile contaminants (e.g., chromium, nitrate, technetium-99, tritium) are useful in identifying tank waste components and mixing trends in groundwater (Johnson and Chou 1998;Hodges 1998). Plots of nitrate/technetium-99 versus technetium-99 ( Figure 5.2) indicate that the data is consistent with the observed groundwater contamination being the result of mobilization and dilution of tank waste by infiltrating surface water.…”
Section: Conceptual Modelmentioning
confidence: 57%
“…The direction of groundwater flow in the vicinity of WMA U has varied because of changing effluent discharge sites within the 200 West &ea (Hodges 1998). The direction of groundwater flow, at the time when the RCIU4 detection network was established, was toward the northeast (Caggiano and Goodwin 1991).…”
Section: Conceptual Modelmentioning
confidence: 99%
“…Johnson and Chou (1998) discuss the extent that rapid snowmelt from recent years has contributed to natural driving forces. The results of a rapid snow melt event in February 1979 are documented in Hodges (1998) with photographs showing extensive flooding in the 241-T Tank Farm. The effects of these events can be enhanced by gravel surfaces, lack of plant uptake and transpiration, and surface depressions that tend to collect and pond run-off and snow melt.…”
Section: Driving Forcesmentioning
confidence: 99%
“…In September 1993 technetium-99 reached a maximum activity of 12,200 pCi/L, 14 times the drinking water standard (DWS) of 900 pCi/L; iodine-129 reached an activity of 64.2 pCi/L, 64 times the DWS; and tritium reached an activity of 564,000 pCi/L, 28 times the DWS. The first determination (Hodges 1998) concluded that: 1) elevated technetium-99 and co-contaminants (e.g., chromium, tritium, nitrate, iodine-129, etc.) in well 299-W14-12 is consistent with a source within the WMA and contaminant chemistry is consistent with a small volume tank waste source; and 2) an upgradient source (the 216-T-25 Trench) is possible.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the first determination (Hodges 1998), a RCRA Facility Investigation/Corrective Measures Study (RFI/CMS) will be initiated at WMA T and WMA TX-TY. The primary focus of the1.7 schedule and activities for the RFI/CMS are described in the Hanford Federal Facility Agreement and Consent Order (Tri-Party Agreement, Ecology et al 1989), Change .…”
Section: Introductionmentioning
confidence: 99%